Congenital mitral valve lesions : Correlation between morphology and imaging - Bo Remenyi; Tom L Gentles (Wolters Kluwer Medknow Publications, 2012)
Congenital malformations of the mitral valve are often complex and affect multiple segments of the valve apparatus. They may occur in isolation or in association with other congenital heart defects. The majority of mitral valve malformations are not simply classified, and descriptive terms with historical significance (parachute, mitral, or arcade) often lack the specificity that cardiac surgeons demand as part of preoperative echocardiographic morphological assessment. This paper examines the strengths and limitations of commonly used descriptions and classification systems of congenitally malformed mitral valves. It correlates pathological, surgical, and echocardiographic findings. Finally, it makes recommendations for the systematic evaluation of the congenitally malformed mitral valve using segmental echocardiographic analysis to assist precise communication and optimal surgical management.